Loss of functional cell surface transforming growth factor β (TGF-β) type 1 receptor correlates with insensitivity to TGF-β in chronic lymphocytic leukemia - DeCoteau, John F. (The National Academy of Sciences of the USA, 1997)
Chronic lymphocytic leukemia (CLL) is the most common form of adult leukemia in Western countries, and there is significant variability in survival within CLL clinical stages. Earlier studies showed that CLL cells produce and are usually growth inhibited by transforming growth factor β type 1 (TGF-β1), suggesting a mechanism for the clinically indolent course of most CLL. Here we studied the mechanism by which CLL cells from about one-third of the patients are insensitive to TGF-β1. Of the 13 patients studied, CLL cells isolated from the peripheral blood of 8 patients were sensitive to growth inhibition by TGF-β1, as determined by incorporation of tritiated thymidine, whereas those from 5 patients were completely resistant to TGF-β1. As judged by binding of radiolabeled TGF-β1 followed by cross-linking and immunoprecipitation with anti-receptor antisera, CLL cells sensitive to TGF-β1 exhibited normal cell surface expression of both types 1 and 2 TGF-β receptors. In contrast, all CLL cells resistant to TGF-β1 exhibited no detectable surface type I receptors able to bind TGF-β1, but normal expression of type II receptors. Both TGF-β1-sensitive and TGF-β1-resistant CLL cells contained normal amounts of both type 1 and type 2 receptor mRNAs. Specific loss of type 1 receptor expression represents a new mechanism by which cells acquire resistance to TGF-β1-mediated growth inhibition in the development and progression of human lymphoproliferative malignancies.